CURATOR'S LEGAL EFFORTS AGAINST BANKRUPTCY ESTATE (BOEDEL) ASSETS SEIZED IN CRIMINAL CONFISCATION OF CORRUPTION CASES - Ida Ayu Putri Dita Helena; I Gusti Ayu Putri Putri Kartika (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2024)
This paper aims to analyze the legal aspects of the general seizure and criminal seizure in Indonesian positive law, as well as to understand the legal efforts of the curator towards the assets of bankrupt estates placed under criminal seizure for corruption and economic crimes. The method used in writing this article is the normative legal research method, which starts from the normative problem of conflict of norms, and the results of this journal article are to determine the position of general seizure and criminal seizure based on the principle of legal preference, namely the principle of lex superior derogat legi inferiori, lex posterior derogate legi priori, and lex specialis derogate legi generalis, and the legal efforts that can be taken by the curator when the assets of bankrupt estates are placed under criminal seizure is by filing an objection to the Corruption Court and by filing a pretrial against the seizure actions carried out by the corruption investigators. The legal status of general attachment and criminal attachment can be determined by the principles of legal preference, including lex superior derogat legi inferiori, lex posterior derogate legi priori, and lex specialis derogate legi generalis. In most cases, general attachment takes priority over criminal attachment, except in cases of corruption (tipikor). In such cases, neither general nor criminal attachment can take precedence over the other. If criminal attachment is imposed on a bankrupt estate, the Curator can file an objection with the Corruption Court within two months of the court decision.